Pengaruh Belanja Langsung Dan Belanja Tidak Langsung Terhadap Pertumbuhan Ekonomi Kabupaten Badung 2001-2010 - Purnama Putra, I Gede Dwi; Adigorim, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 1, No. 2, Desember 2012, 2012)
This research is intended to determine whether partial simultaneouslyand there is significant influence between direct expenditure and indirect expenditure on economic growth in Badung regency in 2001-2010. Based of the results of the analysis are known, that there was a significant correlation between direct expenditure and indirect expenditure on economic growth in Badung regency in 2001-2010. Based on f –test statistic (simultaneously test) found that simultaneously direct expenditure and indirect expenditure have a significant effect on economic growth in Badung regency in 2001-2010 with a confidence level of 99 %.based on t-test (partial test) found that direct spending partiallyhas a positive and significant impact on economic growth at 95% confidence level.while partially indirect spending has a positive and significant impact on economic growth in Badung regency on the level of trust 99%.
Keywords: direct spending; economic growth; indirect spending